Evaluating the Socio-Economic Effects of Fly Ash and Agricultural Waste on the Construction Sector - Irwanda Laory; Januarti Jaya Ekaputri; Andri Kusbiantoro; Raden Aswin Rahadi; Davin H. E. Setiamarga; Augusta Adha; Kurnia Fajar Afgani (Journal Integration of Management Studies, 2024)
The building industry significantly impacts environmental degradation due to its reliance on conventional materials such as cement and concrete, which are associated with high carbon emissions and substantial energy consumption. This study explores the socio-economic impacts of substituting fly ash and agricultural waste for traditional construction materials. A comprehensive review of 50 peer-reviewed papers, industry reports, and online sources reveals that these alternative materials offer considerable benefits. Cost savings average between 15% and 20%, driven by reduced material costs and lower disposal requirements. Environmentally, using fly ash and agricultural waste significantly reduces greenhouse gas emissions, with fly ash cutting emissions by approximately 25% and agricultural waste by about 20%, primarily due to decreased energy consumption. Furthermore, technical assessments show that these materials enhance the strength and durability of concrete, meeting or exceeding conventional standards. The study also highlights broader socio-economic advantages, including support for rural economies through new markets for agricultural by-products and job creation in recycling and construction sectors. These findings suggest integrating fly ash and agricultural waste into construction practices can positively impact economic growth and environmental sustainability. However, the study acknowledges limitations such as reliance on secondary data and potential geographic biases. Future research should prioritize original data collection, long-term performance assessments, and investigation of regional material-use variations. This study underscores the practical and environmental benefits of incorporating these sustainable materials, contributing to a more eco-friendly construction industry.